A Hundred Experiences of Liver Transplantation in Local University Hospital. (July 2018) - Kim, Tae-Seok; Lee, Jeong Woo; Ahn, Keun Soo; Kim, Yong Hoon; Kim, Hyoung Tae; Kang, Koo Jeong
Abstract : Introduction: Liver transplantation (LT) is the complex and challenging procedure in preoperative work-up, surgical techniques, postoperative care, management of complications and out-patients follow-up. For these reasons, it is difficult to build up the liver transplantation program independently in small volume center and most cases of LT had been performed in a few high volume centers. However, many centers have been trying to launch the liver transplantation program recently for a local population who needs LT but has limited opportunity due to the cost and conditions. In here, we introduce our experiences and outcomes of 100 cases of LT as a small volume center. Method: From November 2002 to July 2017, 100 patients were received LT in Keimyung University Dongsan Medical Center. On March 2014, we renewed the LT program by reinforcement of trained staff and establishment of complemented protocol. Fifty cases of LT were performed before renewal of LT program on March 2014 and 50 cases were performed after that time. We reviewed the outcomes of these 100 cases of LT retrospectively. Results: Among 100 cases of LT, DDLT was performed in 60 cases and LDLT in 40 cases. The indications of LT were liver cirrhosis due to HBV in 62 patients, HCV in 7 patients, alcoholics in 30 patients, other causes in 10 patients and hepatocellular carcinoma in 34 patients. The perioperative mortality rate was 18 % before 2014, but decreased to 2 % after renewal (p<0.001). The 3-year survival rate was 74% before 2014, but improved to 95% after renewal (p<0.001). The rate of complications was also improved after renewal of LT program. After renewal of LT program, the outcomes of LT have been more improved and comparable to those of big centers. Conclusion: It is challenging to establish stabilized LT program in small volume center due to complexity and difficulty in operative technique and management of complications. Small volume centers need long time to experience sufficient cases for overcoming learning-curve and stabilizing program independently due to small number of cases. The recruitment of trained and experienced member or support from big centers can be considered for establishment of comparable LT program to big centers in a short period of time and stable LT program in small volume center can provide a practical service for a local population.